Analysis of Students’ Reading Comprehension Achievement in Doing High Order Thinking Skill (HOTS) in School Final Exam - Fadila, Nur; Husnayaini, Ihda; Indrawati, Indrawati (English Education Department, 2021)
The objectives of the study are to measure students’ reading comprehension achievement in doing HOTS and to find out the percentage of HOTS in English reading comprehension in school final examination at SMAN 1 Mendo Barat, Bangka. The sample of this study were two classes with total number of 69 students. In this study, the researcher used students’ test results as the instruments for collecting data. The results of HOTS in reading comprehension was then analyzed by using analysis card listed in the revised edition of Bloom’s taxonomy. It showed that the mean of students’ absorption in answering HOTS in reading comprehension correctly was 35,79% and categorized as bad. Furthermore, the percentage of HOTS in reading comprehension in UAS was 25 % of 40 multiple choice test items, without the evaluation and creation skills and 10 questions represented analysis skill. Therefore, the researcher found that the factors of students’ difficulties in doing HOTS are 1) lack of interest in reading English texts, 2) having no idea the purpose of English reading texts and 3) not accustomed to make conclusions or interpret the texts due to being lack of vocabulary.